The Impact of Personalized Marketing on the Effectiveness of Logistics Solutions in Retail - Semenda, Olha; Poveshchenko, Maksym; Makushok, Olga; Korman, Iryna; Lementovska, Valentyna (International Review of Management and Marketing, 2025)
The aim of the study is to assess the correlation between the degree of marketing personalization and logistic efficiency. The analysis covers international data from seven nations over the period of 2020-2024. The selected countries include the United States, Great Britain, Germany, Poland, Saudi Arabia, China, and Ukraine. The research employed an econometric nonlinear model including indicators of AI, cross-border trade, regulatory frameworks as well as GDP. The findings revealed that the United States (up to 90.2), Germany (up to 89.0), and China (up to 88.7) exhibit the highest levels of logistical efficiency. In nations characterized by a heightened degree of personalized marketing, logistics demonstrate greater adaptability and a more rapid response to market fluctuations. For instance, in the United States, personalized marketing surged from 41.7 to 62.9, coinciding with an increase in exports from 10% to 34.5%. Ukraine exhibited positive dynamics despite a low GDP, with marketing rising from 30.1 to 55.6 and logistics improving from 61.8 to 74.1. The article emphasizes the necessity for institutional support to facilitate the digital transformation of logistics. Prospective avenues for future research include the exploration of behavioral factors and time lags in marketing influences.